Determination of Sites of Special Importance for the Conservation of Threatened Orchid Species in Colombia - Alba-Patiño, Daniela; Martínez-Hernández, Fabian; Mota Poveda, Juan Francisco (Mediterranean Botany, 2021)
Colombia is the country with the highest number of orchid species (4270), whose optimal habitat is cold and humid forests. However, the outlook for conservation is alarming, considering that deforestation is causing the loss of millions of hectares of forests. This situation has led to the existence of 206 endangered orchid species. Therefore, this research was conducted to determine Sites of Special Importance for the Conservation of Threatened Orchid Species in Colombia (SSICO), through an analysis of their spatial and altitudinal distribution using various databases, to make a selection of nature reserves on a municipality scale, using Marxan software, and employing relevant parameters (richness, rarity, and IUCN category). Furthermore, the results were later compared with the Protected Areas System, determining their coverage to propose SSICOs. 674 records of the presence of threatened orchids in 277 municipalities were obtained. Urrao, Abrego, and Frontino were the areas with the greatest richness and rarity. Marxan selected 47 municipalities located mostly in the Andes region, and four SSICOs were prioritized, which are located in the Antioquia, Norte de Santander, Nariño and Putumayo provinces. These SSICOs, in addition to being points of great biodiversity, are areas with special socio-economic characteristics that influence the management of natural resources. These areas require timely attention, research, and intervention by environmental authorities because of their importance for conserving orchids and Andes Forests.